(untitled) (Third Sector Social Economic Review, 2026)
The purpose of this study is to examine the factors influencing sustainable consumption behavior based on the Theory of Planned Behavior (TPB) and the Value-Belief-Norm (VBN) Theory, to reveal how the concept of sustainability is reflected among consumers, and to determine the extent to which perceived price affects the relationship between intention and behavior. For this purpose, a survey was conducted with 403 participants across Turkey, and the collected data were analyzed using the SmartPLS software. During the analysis process, the Partial Least Squares Structural Equation Modeling (PLS-SEM) method was applied. Within the scope of the integrated model, the effects of the TPB and VBN variables on sustainable consumption behavior and the moderating role of perceived price were examined. The findings indicate that the effect of altruistic (self-transcendent) values on the New Ecological Paradigm, as proposed in the VBN theory, and the effect of subjective norm on behavioral intention, as suggested by the TPB, were found to be insignificant. On the other hand, the relationships among the other variables were found to be significant and consistent with the causal chain proposed by both theories. Furthermore, the results revealed that perceived price does not have a moderating effect on the relationship between behavioral intention and sustainable consumption behavior. Furthermore, the results revealed that perceived price does not have a moderating effect on the relationship between behavioral intention and sustainable consumption behavior.